2022
DOI: 10.1002/jcu.23258
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnostic value of periampullary mass: A nomogram established by random forest based on clinical characteristics and contrast‐enhanced ultrasound

Abstract: Purposes: To develop a nomogram model for distinguishing benign from malignant ampullary lesions more intuitive and accurate. Materials and Methods: A total of 124 patients with periampullary lesions from January 2016 to June 2020 were enrolled in this retrospective study. Their clinical information, ultrasound (US), dual contrast-enhanced ultrasound (DCEUS) and MRI image features were used for research. Twenty features were collected in our study. Random forest was used to select the first five most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…3 This is the first article creating a new contrast-enhanced sonography (CEUS)-related nomogram for differentiating benign from malignant lesions in the periampullary area. 3 The periampullary region is a complex area composed of three histologically and physiologically different anatomical structures, namely, ampulla of Vater, pancreatic duct, and common bile duct. 4 Theoretically, clinical and biological behaviors of the diseases depend on their primary pathological structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 This is the first article creating a new contrast-enhanced sonography (CEUS)-related nomogram for differentiating benign from malignant lesions in the periampullary area. 3 The periampullary region is a complex area composed of three histologically and physiologically different anatomical structures, namely, ampulla of Vater, pancreatic duct, and common bile duct. 4 Theoretically, clinical and biological behaviors of the diseases depend on their primary pathological structure.…”
mentioning
confidence: 99%
“…In this study, the authors retrospectively analyzed the data of 124 patients with periampullary disease who underwent histological examination and they identified that patient's age, CBD diameter, enhancement pattern of arterial phase, wash-out pattern of venous phase, lesion size after CEUS as five most important indicator of disease characteristics, and, based on this, created a nomogram that predict the disease differentiation between benignity and malignancy. 3 The authors should be praised for suggesting a new nomogram that showed nomogram to be highly diagnostic of periampullary diseases: the area under curves (AUC) and 95% confidence intervals (CI) for nomogram, magnetic resonance imaging (MRI) + MRCP+CEUS (combination of subjective diagnosis by the sonographer and radiologist), CEUS (subjective diagnosis by sonographer), MRI + MRCP (subjective diagnosis by radiologist) were 0.98, 0.91, 0.89, and 0.68 respectively. 3 However, there are some points to consider about this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation